Fomo, Virality, and Saturation: A Netnographic Study of Digital Consumer Behavior towards the Mixue Brand in Indonesia - Sandra J.R Kainde; Harke Revo Leonard Polii (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to analyze digital consumer behavior toward the Mixue brand in Indonesia within the dynamics of Fear of Missing Out (FOMO), virality, and saturation through a netnographic approach. Employing a qualitative design, this research uses netnography to examine digital interaction traces within Mixue's online ecosystem in Indonesia, including posts, comments, memes, conversations, and other forms of symbolic participation on social media. The findings indicate that digital consumer behavior toward Mixue develops along a dynamic trajectory. In the initial phase, FOMO stimulates consumer engagement, as Mixue is positioned as a social experience that must be followed in order not to be left behind in the flow of digital trends. This engagement subsequently evolves into virality, sustained through electronic word of mouth (eWOM), meme production, collective humor, and the symbolic participation of netizens. However, the continuous intensity of exposure and symbolic reproduction does not necessarily strengthen affection toward the brand; instead, it generates saturation that shifts engagement from enthusiasm to critical evaluation. In addition, the negotiation of trust and legitimacy suggests that the relationship between digital consumers and the brand is shaped not only by trend-driven logic but also by the need for validation and a sense of security. These findings confirm that digital consumer behavior toward a viral brand is a relational, symbolic, and constantly evolving cultural process.